New Current-Mode Oscillators Using Unity-Gain Current-Followers - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A catalog of current-mode oscillator circuits using negative unity-gain current-followers is presented. Each circuit uses two unity-gain current-followers, three resistors, and three capacitors . Simulation results obtained from two new circuits are presented.